The Effect of Clove Leave Essential Oil (Syzigium aromaticum, L) on Mortality Level of Aedes aegypty Mosquitos - Iva Ariska (Journal of Public Health and Pharmacy)
One of the big problems in Indonesia is dengue hemorrhagic fever caused by the Aedes aegypti mosquito. The use of natural materials as a safe control for health and environmentally friendly is an option for the community. Clove leaves contain compounds of eugenol, saponins, flavonoids, and tannins. The purpose of this study is to determine the effect of clove leaf essential oil, Syzygium aromaticum, L. on the level of Aedes aegypti Mosquito mortality.